2017
DOI: 10.1021/acsnano.7b05191
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and High-Color-Purity Light-Emitting Diodes Based on In Situ Grown Films of CsPbX3 (X = Br, I) Nanoplates with Controlled Thicknesses

Abstract: We report a facile solution-based approach to the in situ growth of perovskite films consisting of monolayers of CsPbBr nanoplates passivated by bulky phenylbutylammonium (PBA) cations, that is, two-dimensional layered PBA(CsPbBr)PbBr perovskites. Optimizing film formation processes leads to layered perovskites with controlled n values in the range of 12-16. The layered perovskite emitters show quantum-confined band gap energies with a narrow distribution, suggesting the formation of thickness-controlled quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
189
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(201 citation statements)
references
References 53 publications
9
189
1
Order By: Relevance
“…Similar to MAPbBr 3 , 2D FAPbBr 3 NPLs can be very efficient emitters. Recently, with about 7–10 unit cells colloidal FAPbBr 3 NPLs, Kumar et al have reported a pure green LED [128]. The exciton-binding energy as high as 162 meV for 2D FAPbBr 3 perovskites via the dielectric quantum well engineering.…”
Section: Approaches To Achieve Npl-ledsmentioning
confidence: 99%
“…Similar to MAPbBr 3 , 2D FAPbBr 3 NPLs can be very efficient emitters. Recently, with about 7–10 unit cells colloidal FAPbBr 3 NPLs, Kumar et al have reported a pure green LED [128]. The exciton-binding energy as high as 162 meV for 2D FAPbBr 3 perovskites via the dielectric quantum well engineering.…”
Section: Approaches To Achieve Npl-ledsmentioning
confidence: 99%
“…External quantum efficiency >10% [10,11] and ultrahigh brightness up to 5.9×10 5 cd m −2 [12] have been reported. The work of Becker et al reinforces the idea that lead halide perovskites are excellent light emitters.…”
Section: Haiping Hementioning
confidence: 99%
“…As mentioned above, the quasi 2D PNC structure can be denoted as L 2 A n−1 B n X 3n+1 . Plenty of investigations have been conducted on the choices of bulky cation L, including PEA, [56,63,64,[89][90][91][92] BA, [55,88,[93][94][95] ethylammonium (EA), [96] phenylmethylamine (PMA), [97] phenylbutylammonium (PBA), [98,99] naphthylmethylamine (NMA) [65,100] and 2-Phenoxyethylamine (POEA). [101] Similar to the pure 2D structure, with the space dimension reduced to nanosized 3D or quasi 2D, the PNCs exhibit strong excitonic behavior.…”
Section: Organic Ammonium Assisted In Situ Fabricationmentioning
confidence: 99%
“…Nevertheless, it seems in some works that large OA cations can solely assist the in situ fabrication of PNCs without the participation of antisolvent. [65,98] Therefore, in contrast to the great success of film optimization, the understanding into the role of OA cations as well as antisolvents in the crystalline kinetics falls behind and needs to be clarified.…”
Section: Organic Ammonium Assisted In Situ Fabricationmentioning
confidence: 99%
See 1 more Smart Citation